CRACKING THE GLASS CEILING: UNVEILING THE RESILIENCE AND PERSISTENCE OF WOMEN LEADERS IN SENIOR LEADERSHIP WITHIN THE NAMIBIAN HIGHER EDUCATION - Ms Klaudia Ndakolonkoshi; Zvisinei Moyo; Clive Smith (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
There is a growing body of study and interest worldwide concerning the experiences of women in senior leadership roles in higher education institutions (HEIs). Hence, this study examined persistence of women leaders in senior leadership positions in the HEIs in Namibia. To gather the lived experiences and narratives of female leaders taking senior leadership positions the study combined qualitative methods with a critical paradigm-supported phenomenological case study design. Thematic analysis was used to semi-structured interview data, emphasising recurrent themes, patterns, and important topics. The study's findings were theoretically interpreted using feminist and role modelling motivation theories. Findings reveal that women leaders’ leadership experiences have been influenced by their attendance at conferences, seminars, and workshops. They made a positive difference in the lives of their colleagues and fostered a positive work environment. They have also inspired other women to aspire to leadership roles. By shedding light on these experiences, the study enriches understanding of gender dynamics in academic leadership, providing valuable insights for institutions striving towards gender equity and inclusive leadership. It sheds light on the strategies that contribute to their sustained success in senior roles. Future researchers should consider collecting data from aspiring women leaders so that there would be informed comparisons of their experiences. In addition to investigating the experiences of male leaders in senior leadership roles and establishing their perspectives of women leaders in senior leadership positions, future researchers should examine the impact of mentoring on career advancement and retention of women in senior leadership positions.